Crime, pandemic and social mobility: empirical evidence from Türkiye - Çalışkan, Aykut (Crime, law and social change, 2024)
Criminal behavior, which takes its content from society, has been associated with social isolation, national quarantine, and mandatory stay-at-home measures during the COVID-19 pandemic, and it has been researched through crime rates. Moreover, it has been argued that changes in the level of social mobility also affect crime rates. Decreased crime rates have been reported during closure measures, and a significant literature has emerged based on these propositions. This study's retrospective approach was created to examine the appearance of crime rates in Türkiye. The main problem of the research is to reveal the relationship between crime, pandemic, and social mobility in Türkiye. For this purpose, it aimed to test the propositions based on a dual approach. First, patterns in crime rates were discovered. The data set regarding the most common crime types between 2018 and 2022, including pre-pandemic crime rates, was used. The most appropriate time series model was determined to understand the data structure regarding crime types, and it was tested whether there was a decrease or increase in crime rates during and after the pandemic. As a second step, the effect of social mobility on the change in crime was examined according to the mobility level data reported in this process. Evidence has shown decreased violence, theft, and drug crimes in the early part of the pandemic, consistent with the literature. While theft crimes decreased throughout the pandemic, violence and drug crimes increased. The view that crime rates will decrease if social mobility is restricted as a source of social life presented overlapping data in the pandemic. Changes in social mobility during the pandemic have affected crime rates for theft, injury, and drug use. Although there was a decrease in crime rates due to seasonal effects after the normalization process, it was observed that crime rates could change according to the content of social measures during the pandemic period. It is considered that this situation presents a particular slice for the future.